Studi Deskriptif Proporsi Jenjang Kognitif dan Afektif Soal Ujian Sekolah Mata Pelajaran pendidikan pancasila dan kewarganegaraan Siswa SD/MI Kota Bengkulu Tahun Pelajaran 2019/2020 - Eka Darianti Br. Ginting; Herman Lusa; Dwi Anggraini (Universitas Bengkulu, 2020)
The problems that occur so far, the teacher has never measured the proportion of questions in basic competencies at each level of Pancasila and Citizenship Education subjects. So it is not yet known the distribution of questions in the school exams in Pancasila and Citizenship Education subjects. In addition, the reality that occurs in the field is that the questions made by the teacher in the exam are mostly only focused on the cognitive realm, even though for Pancasila and Citizenship Education subjects, the affective domain is also implicit in Permendikbud No. 37 of 2018. This study aims to describe the proportion of questions in basic competencies per class level, cognitive level, affective level of school exam questions in Pancasila and Civics Education subjects in Bengkulu City SD / MI students for the 2019/2020 academic year. This type of research is descriptive research. The subjects in this study were Class VI SD / MI Bengkulu City. The object in this study is the suitability of the basic competencies of grades IV, V, and VI with school exam questions, school exam questions, the proportion of cognitive levels, the proportion of affective levels of school exam questions for Pancasila education subjects and the citizenship of SD / MI students in Bengkulu City for the 2019 academic year / 2020. The research instrument used was documentation in the form of school exam questions for Pancasila Education and Citizenship of SD / MI students of Bengkulu City for the 2019/2020 academic year. The research data were analyzed using the proportion of the cognitive level of the affective on the items analyzed then the percentage was calculated. The results showed that: 1) The proportion of questions in basic competence per class level, including the basic competency of class VI as many as 4 percentage items of 10%, class V of 9 percentage items of 22.5% and class VI of 27 items a percentage of 67.5%; 2) The proportion of cognitive level, including the level of understanding (C2) as many as 11 items of 27.5%, applying (C3) of 8 items of 20%, analyzing (C4) of 15 items of 37.50%, and evaluating (C5)) as many as 6 items at 15%. Based on the analysis, the recall level (C1) and the creative level (C6) were not yet in the items on the school exam; 3) The proportion of the affective level, including the response level (A2) as many as 5 percentage items of 12.5%, the respect level (A3) as many as 15 items, the percentage of 37.5%, the organizing level (A4) as many as 8 percentage questions 20%, and the level of characterization according to value (A5) is 5 items, the percentage is 12.5%. Thus it can be concluded that the items in the PPKn subject school exam for the 2019/2020 school year have known the proportion of the number of questions in basic competencies per class level, the proportion of cognitive levels and affective levels.Keywords: suitability of basic competencies, cognitive level, affective level.